Programa de intervenção cognitivo-comportamental para cuidadores-familiares de idosos com demênciaA - Patricia Paes Araujo Fialho (2010)
One of the main concerns among specialists in the area of health and ageing regards dementia and the far reaching repercussions for the family and the caregiver, especially when he or she happens to be the member of the first one. Dementia is usually chronic and progressive, such that the patients ability to lead an independent life deteriorates day by day, making him or her more and more dependent on others. In addition, the behavioral and psychological symptoms of dementia (BPSD) diminish patient, family and caregiver quality of life and represent one of the most important reasons for institutionalization. As a result, there is a growing literature about the benefits of intervention programs for dementia patient caregivers. Many of these intervention programs seem to be effective in reducing burden and depression among caregivers. Cognitive behavioral therapy (CBT) appears to be particularly efficient in decreasing depressive symptoms (Prince et al., 2009). This scenario points to the importance of conducting studies such as the one we currently present in order to elaborate, implement and evaluate a Cognitive Behavioral Intervention Program. The total sample included 40 caregivers and their family member with dementia. The intervention was based on CBT techniques, involving eight sessions, once a week. The cognitive, functional and behavioral status of the patients was evaluated as well their own and their family caregivers perceptions of quality of life. With the purpose of studying burden related to caretaking activities several instruments were applied to estimate stress level, coping, anxiety and depression. They present in average 53 years of age and 8 year education. Most of them have income between 1 and 3 minimum wage and total timing dedication to the patient. They are inexperienced in the whole of caregiver and have little information on the illness of the relative they are in charge of. At the end of the program we observed fewer BPSDs, an increase in the patients quality of life (according to the caregivers), changes in the use of coping strategies, and a significant decrease in anxiety levels. As such, The Cognitive Behavioral Intervention Program appears to be a promising and useful tool for the relief of factors that reduce the caregivers quality of life.